Fostering Creativity Among Secondary School Adolescents: Roles of Mothers and Teachers - U.E, Nnubia; W.N, Madichie (Journal of Home Economics Research, 2024)
This study investigated roles of mothers and teachers in fostering creativity among secondary school adolescents. It was a survey. Three research questions guided the study. The population comprised of all mothers in Federal College of Education (Tech), Umunze and all the secondary school teachers in Orumba-South Local Government Area of Anambra-State. Questionnaire was used for data collection and mean was used for analysis. Findings include; 10 factors militating against fostering creativity among secondary school adolescents, 8 roles of mothers and 8 roles of teachers for fostering creativity among secondary school adolescents were also identified. Based on the findings, recommendations were made which include parents especially mothers providing materials and encouraging creative activities among their adolescent children to increase their cognitive flexibility and idea generation skills.